Sustainable Trade in the Ixil Triangle, Guatemalan Highlands - Radulescu, Angela (Consilience, 2011)
Guatemala has among the largest numbers of indigenous people living within its borders in Central America. With wealth coming from tourism and exports concentrated mainly around Guatemala City, descendants of the ancient Maya live in small, ethnically distinct villages where locals struggle to preserve their heritage. Isolated in the valleys between the Cuchumatanes Mountains, the Ixil Triangle is home to a unique community of Ixil people who have retained their ancient way of life. Men tend to be farmers, women weave using technologies passed down from generation to generation, and few have a strong grasp of Spanish as a second language. Yet despite the isolation, tensions and instability in modern-day Guatemala have struck this community hard. A startling number of the indigenous citizens of Guatemala, who make up 40% of the population, have no access to education, and many have no voice in the political process, as they lack the financial means to pay to become registered citizens. The Ixil also face economic pressures, as well as the repercussions of a bloody civil war that ended in 1996, taking an entire generation of men as casualties. Faced with the prospect of their disappearing culture, a small group of widows in the village of San Juan Cotzal have welcomed the help of European volunteers, and formed a weaving co-op. They take orders from distributors in more established tourist stops like Guatemala City and Antigua, utilizing age-old technologies to make carpets, bags, shawls, and other products that volunteers then deliver to stores around the country. Building upon the business skills they gain by maintaining the co-op, the widows are both politically and economically active, taking initiative on behalf of their community. Future projects include organizing fundraisers to equip each widow’s home with proper stoves and developing an improved outreach strategy to goods distributors in the larger cities. Defying heavy odds, the empowered women of Ixil are finding local ways to integrate their heritage into the global landscape.